LINGUISTIC FIELD THEORY IN THE LIGHT OF LINGUOCULTUROLOGY: THE FIELD PRINCIPLE OF THE STRUCTURE OF THE LANGUAGE SYSTEM - Aripova Dilnoza Vakhobjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the modern world, where there is active cultural exchange and population migration, the study of the lexical-semantic field “family” in different cultures is becoming increasingly relevant and necessary for successful intercultural communication. This article outlines some issues of linguistic field theory in the light of linguoculturology: the field principle of the structure of the language system.